Effects of cerebral ischemia in mice deficient in Persephin - Tomac, Andreas C. (National Academy of Sciences, 2002)
Persephin (Pspn), a recently cloned member of the transforming growth factor-β superfamily (TGF-β) and glial cell line-derived neurotrophic factor (GDNF) subfamily, is distributed throughout the nervous system at extremely low levels and is thought to function as a survival factor for midbrain dopaminergic and spinal motor neurons in vivo. Here, we report that mice lacking Pspn by homologous recombination show normal development and behavior, but are hypersensitive to cerebral ischemia. A 300% increase in infarction volume was observed after middle cerebral artery occlusion. We find that glutamate-induced Ca(2+) influx, thought to be a major component of ischemic neuronal cell death, can be regulated directly by the Persephin protein (PSP) and that PSP can reduce hypoxia/reperfusion cell death in vitro. Neuronal cell death can be prevented or markedly attenuated by administration of recombinant human PSP in vivo before ischemia in both mouse and rat models. Taken together, these data indicate that PSP is a potent modulator of excitotoxicity in the central nervous system with pronounced neuroprotective activity. Our findings support the view that PSP signaling can exert an important control function in the context of stroke and glutamate-mediated neurotoxicity, and also suggest that future therapeutic approaches may involve this novel trophic protein.